Global ultrasound assessment of structural lesions in osteoarthritis: a reliability study by the OMERACT ultrasonography group on scoring cartilage and osteophytes in finger joints. Issue 2 (17th December 2014) - Hammer, H B; Iagnocco, A; Mathiessen, A; Filippucci, E; Gandjbakhch, F; Kortekaas, M C; Möller, I; Naredo, E; Wakefield, R J; Aegerter, P; D'Agostino, M-A
Abstract : Objective: Ultrasonography is sensitive for the evaluation of cartilage pathology and degree of osteophytes in patients with hand osteoarthritis (OA). High consistency of assessments is essential, and the OMERACT (Outcome Measures in Rheumatology) ultrasonography group took the initiative to explore the reliability of a global ultrasonography score in patients with hand OA using semiquantitative ultrasonography score of cartilage and osteophytes in finger joints. Methods: Ten patients with hand OA were examined by 10 experienced sonographers over the course of two days. Semiquantitative scoring (0–3) was performed on osteophytes (carpo-metacarpal 1, metacarpo-phalangeal (MCP) 1–5, proximal interphalangeal 1–5 and distal interphalangeal 2–5 joints bilaterally with an ultrasonography atlas as reference) and cartilage pathology (MCP 2–5 bilaterally). A web-based exercise on static cartilage images was performed a month later. Reliability was assessed by use of weighted κ analyses. Results: Osteophyte scores were evenly distributed, and the intraobserver and interobserver reliabilities were substantial to excellent (κ range 0.68–0.89 and mean κ 0.65 (day 1) and 0.67 (day 2), respectively). Cartilage scores were unevenly distributed, and the intraobserver and interobserver reliability was fair to moderate (κ range 0.46–0.66 and mean κ 0.39 (day 1) and 0.33 (day 2), respectively). The web-based exercise showed acceptable agreement for cartilage being normal (κ 0.47) or with complete loss (κ 0.68), but poor for the intermediate scores (κ 0.22–0.30). Conclusions: Use of the present semiquantitative ultrasonography scoring system for cartilage pathology in hand OA is not recommended (while normal or total loss of cartilage may be assessed). However, the OMERACT ultrasonography group will endorse the use of semiquantitative scoring of osteophytes with the ultrasonography atlas as reference.